Performance of Fighting Brands in Maintaining Market Share in Cement Trading during Oversupply - Abdul Aziz; Ratni Prima Lita; Yulia Hendri Yeni; Veri nita; Alfit man (Politeknik Negeri Bengkalis, 2023)
Since March 2020 there has been a slowdown in infrastructure development which has resulted in a slowdown in the cement trade. The actual production of the Indonesian national cement company in 2021, which is under the BUMN Ministry, is 52.6 million tonnes. In the same year, sales realization until the end of December 2021 was only 40.469 million tonnes or only 76.94% of production capacity. At the end of 2021, there was an excess of national cement production capacity in Indonesia of 53.8 million tonnes. The purpose of the review is to find references for the application of fighting brands as a strategy to maintain market share in cement sales to cement producers. It was found the potential to use fighting brands in the cement trading sector in conditions of oversupply to maintain market share and loyal customers so as not to switch to other brands considering the cement trading market is a market with perfect competition. Even though the concept of fighting brand or fighter brand strategy was developed in the 1980s by Al Ries and Jack Trout, fighting brands are still widely used by manufacturing companies and service companies to win competition in the global market when there is oversupply. The ten reputable articles we have selected for this review have provided marketing managers with insights from research results on the positive effect of fighting brands in maintaining and increasing sales performance. We advise marketing managers in the cement industry and cement distributors to explore how to implement the use of fighting brands in the cement sector business when oversupply